2020
DOI: 10.3389/fmicb.2019.03081
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Reveals the Architecture of Granulomatous Lesions Caused by Tuberculosis and Mycobacterium avium Complex Lung Disease

Abstract: Tuberculosis (TB) and Mycobacterium avium complex lung disease (MAC-LD) are both characterized pathologically by granuloma lesions, which are typically composed of a necrotic caseum at the center surrounded by fibrotic cells and lymphocytes. Although the histological characterization of TB and MAC-LD granulomas has been well-documented, their molecular signatures have not been fully evaluated. In this research we applied mass spectrometry-based proteomics combined with laser microdissection to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Several species of Mycobacterium exist as intracellular pathogens in acidic and hypoxic environments ( Sibling et al, 1987 ; Oh and Straubinger, 1996 ; Rastogi et al, 2001 ; Houben et al, 2006 ; Benítez-Guzmán et al, 2019 ; Seto et al, 2020 ). In order for phage therapy to be efficient against such mycobacterial infections, phages need to retain their activity and infectivity in these extreme environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of Mycobacterium exist as intracellular pathogens in acidic and hypoxic environments ( Sibling et al, 1987 ; Oh and Straubinger, 1996 ; Rastogi et al, 2001 ; Houben et al, 2006 ; Benítez-Guzmán et al, 2019 ; Seto et al, 2020 ). In order for phage therapy to be efficient against such mycobacterial infections, phages need to retain their activity and infectivity in these extreme environments.…”
Section: Resultsmentioning
confidence: 99%
“…Various Mycobacterium species ( M. tuberculosis , M. avium complex, M. bovis , and M. leprae ) are found to reside intracellularly at low pH conditions which poses a challenge in efficacy of anti-bacterials ( Sibling et al, 1987 ; Oh and Straubinger, 1996 ; Ehlers and Schaible, 2012 ; Benítez-Guzmán et al, 2019 ). M. tuberculosis and M. avium complex also form granulomatous structures, marked by a gradient of hypoxia, nutrient deprivation and acidity ( Timm et al, 2003 ; Voskuil et al, 2004 ; Lawn and Zumla, 2011 ; Ehlers and Schaible, 2012 ; Seto et al, 2020 ). For a phage to successfully eliminate these bacilli, it needs to be active and efficient under such low pH and hypoxic conditions and should be able to enter into the eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of Mycobacterium exist as intracellular pathogens in acidic and hypoxic environments (Sibling et al, 1987; Oh and Straubinger, 1996; Rastogi et al, 2001; Houben et al, 2006; Benítez-Guzmán et al, 2019; Seto et al, 2020). In order for phage therapy to be efficient against such mycobacterial infections, phages need to retain their activity and infectivity in these extreme environments.…”
Section: Resultsmentioning
confidence: 99%
“…Various Mycobacterium species ( M. tuberculosis , M. avium complex, M. bovis and M. leprae ) are found to reside intracellularly at low pH conditions which poses a challenge in efficacy of anti-bacterials (Sibling et al, 1987; Oh and Straubinger, 1996; Ehlers and Schaible, 2012; Benítez-Guzmán et al, 2019). M. tuberculosis and M. avium complex also form granulomatous structures, marked by a gradient of hypoxia, nutrient deprivation and acidity (Timm et al, 2003; Voskuil et al, 2004; Lawn and Zumla, 2011; Ehlers and Schaible, 2012; Seto et al, 2020). For a phage to successfully eliminate these bacilli, it needs to be active and efficient under such low pH and hypoxic conditions and should be able to enter into the eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Liquefied caseum that reaches an adjacent airway stimulates the cough reflex facilitating bacterial dissemination ( Marakalala et al, 2016 ). Granulomas caseous centers represent a pro-inflammatory environment characterized by anoxia and the presence of several proteins and lipids deriving from cellular necrosis, as well as reactive oxygen species, pro-inflammatory eicosanoids, and antimicrobial peptides ( Marakalala et al, 2016 ; Seto et al, 2019 ). Sarathy et al (2018) showed that M. tuberculosis residing in caseum is not able to replicate and become highly tolerant to several first‐ and second-line anti tubercular drugs following a trend similar to that observed in in vitro models of non-replicative M. tuberculosis based on hypoxia or starvation.…”
Section: Triacylglicerol Accumulation As a Trigger For Bacterial Hibementioning
confidence: 99%